2017
DOI: 10.5152/eurjrheum.2017.160076
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of serum biomarker of type II Collagen degradation (Coll2-1) by intra-articular injection of an autologous plasma-rich-platelet in patients with unilateral primary knee osteoarthritis

Abstract: Objective: This study aimed to evaluate the effect of one dose of intra-articular injection of (PRP) in the knee joint on a specific osteoarthritis (OA) serum biomarker of cartilage degeneration, Collagen 2-1 (Coll2-1), over a short period of 3 months. The aim extended to clarify the effect of PRP on the functional status of the osteoarthritic knee joint. Material and Methods:Sixty patients with primary unilateral knee OA were enrolled in this study. They were subdivided according to Kellgren-Lawrence grading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The effect of one dose injection of intra-articular platelet-rich plasma (PRP) in the knee joint on a serum biomarker of cartilage degeneration, Coll2-1 was evaluated over a short period of 3 months. They reported a reduction in Coll2-1 following injection emphasizing that PRP could be a promising safe and tolerable effective therapeutic option 47 . In another study, clinical efficacy of TissueGene-C (TG-C), a cell and gene therapeutic consisting of non-transformed and retrovirally transduced chondrocytes to overexpress TGF-b1 (3:1), was evaluated for KOA patients.…”
Section: Early and Late Assessment Of Intervention Efficacy And Undermentioning
confidence: 99%
“…The effect of one dose injection of intra-articular platelet-rich plasma (PRP) in the knee joint on a serum biomarker of cartilage degeneration, Coll2-1 was evaluated over a short period of 3 months. They reported a reduction in Coll2-1 following injection emphasizing that PRP could be a promising safe and tolerable effective therapeutic option 47 . In another study, clinical efficacy of TissueGene-C (TG-C), a cell and gene therapeutic consisting of non-transformed and retrovirally transduced chondrocytes to overexpress TGF-b1 (3:1), was evaluated for KOA patients.…”
Section: Early and Late Assessment Of Intervention Efficacy And Undermentioning
confidence: 99%
“…Other authors showed a reduction in cartilage catabolism after PRP, through serum peptide of the alpha-helical region of type II collagen. 63 Intra-articular PRP improved the appearance of inflamed synovium, and ultrasound changes (reduced vascularity and less effusion) correlated with clinical outcomes. 64 Calcitonin gene-related peptide expression mediates pain reduction and down-regulation of synovial inflammation induced by PRP.…”
Section: How Work Performed In Oa Phenotyping Might Impact Prp Therapmentioning
confidence: 86%
“…OA is the most prevalent disease of joints in elderly patients, affecting many millions of individuals worldwide and resulting in knee pain and locomotor system disability [ 5 , 22 ]. OA is characterized by intra-articular inflammation, cartilage degeneration, and subchondral bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, this marker can be used as a factor to predict the response to therapy in OA. Collagen and proteoglycans are degradation and lost due to excessive secretion of MMPs and other proteolytic enzymes [ 22 , 28 , 29 ]. The MMP family contains approximately 28 members, which can be divided into subgroups such as collagenases, gelatinases, and stromelysins.…”
Section: Discussionmentioning
confidence: 99%